Dampak Kepemimpinan Transformasional Terhadap Kinerja Dan Loyalitas Pegawai Di Dinas Pemadam Kebakaran Kabupaten Sumbawa Barat - Deni Nurdani; Ivon Arisanti (Jurnal Ilmiah Raflesia Akuntansi, 2025)
Transformational leadership is a leadership style that has a strategic role in improving employee performance and loyalty, especially in public sector organizations such as the West Sumbawa Regency Fire Department. This study aims to test and analyze the effect of Transformational Leadership on Employee Performance and Employee Loyalty in the West Sumbawa Regency Fire Department. This study uses a quantitative approach with a data analysis method through Structural Equation Modeling - Partial Least Squares (SEM-PLS). The population of the study was all employees of the West Sumbawa Regency Fire Department totaling 115 people, with a sampling technique using a census. Primary data were collected through questionnaires that had been tested for validity and reliability, resulting in valid and reliable instruments. The results showed that Transformational Leadership had a positive and very significant effect on Employee Performance with a coefficient value of 0.957 and a t-statistic of 84.960 (p <0.000). In addition, Transformational Leadership also has a positive and significant effect on Employee Loyalty with a coefficient value of 0.938 and a t-statistic of 49.217 (p <0.000). The R-Square value for Employee Performance of 0.916 and for Employee Loyalty of 0.879 indicates that the independent variable is able to explain high variations in both dependent variables. The reliability test also showed very good results with Composite Reliability values> 0.97 and Cronbach's Alpha> 0.96 for all constructs. This study concludes that the implementation of Transformational Leadership is effectively able to improve Employee Performance and Loyalty at the West Sumbawa Regency Fire Department. The implication of this study is the need for training and capacity development for structural leaders to be able to apply the principles of transformational leadership consistently, in order to create a supportive work climate, high intrinsic motivation, and strong commitment to the organization.